SPIRITUAL LEADERSHIP AND ORGANIZATIONAL COMMITMENT IN HIGHER EDUCATION: MEDIATING ROLE OF TRI HITA KARANA AND SPIRITUAL WELLBEING - Putu Gede Subhaktiyasa; Silvia Ni Nyoman Sintari; I Nyoman Bagus Suweta Nugraha; N. Putri Sumaryani (Jurnal Manajemen Pendidikan, 2026)
Spirituality and local wisdom values play an important role in organizational behavior, but their integration into leadership and lecturer commitment in higher education institutions has not been widely explored. This study aims to understand the effect of spiritual leadership on lecturer commitment, mediated by Tri Hita Karana (THK) culture and spiritual wellbeing. The study used an exploratory quantitative design involving 98 lecturers from higher education institutions using the inverse square root and gamma exponential methods. The sample size was determined using purposive sampling, with the criterion that participants be permanent Hindu lecturers holding a minimum functional position of assistant expert. Data analysis used a PLS-SEM second-order reflective model. The results indicate that spiritual leadership impacts organizational commitment, THK, and lecturers' spiritual wellbeing. THK culture and spiritual wellbeing play significant roles as mediators of the effects of spiritual leadership on organizational commitment. These findings suggest that integrating personal spirituality and local cultural values into leadership can strengthen lecturers' commitment. Higher education management needs to develop leadership in harmony with local cultural wisdom and spirituality to foster a harmonious academic environment.